2020
DOI: 10.1016/j.ipej.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy to treat vaso-vagal syncope: Cardiac neuromodulation by cryoballoon pulmonary vein isolation

Abstract: Background Clinical management of vaso-vagal syncope (VVS) remains challenging since no therapy has proven to completely prevent VVS recurrence. Objective The purpose of this study was to analyze the mid-term outcome of cryoballoon (CB) cardioneuroablation achieved by pulmonary vein isolation (PVI) in patients with VVS. Methods Patients who underwent CB cardioneuroablation in our centers between January 2014 to June 2018 were included. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Since then, other investigators have reported the results from smaller observational and one randomized controlled trial to use cardioneuroablation to treat vasovagal syncope, functional AV block or functional sinus node dysfunction. [15][16][17][18][19][20][21][22][23] However, there are still uncertainties with the optimal strategy for the identification of GP sites. In the original description, ablations were directed towards the highest density of the so-called AF-Nests, identified by spectral analysis of the endocardial electrograms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, other investigators have reported the results from smaller observational and one randomized controlled trial to use cardioneuroablation to treat vasovagal syncope, functional AV block or functional sinus node dysfunction. [15][16][17][18][19][20][21][22][23] However, there are still uncertainties with the optimal strategy for the identification of GP sites. In the original description, ablations were directed towards the highest density of the so-called AF-Nests, identified by spectral analysis of the endocardial electrograms.…”
mentioning
confidence: 99%
“…Subsequent ablation at the site of inferior left GP was critical for restoring normal AV conduction. Since then, other investigators have reported the results from smaller observational and one randomized controlled trial to use cardioneuroablation to treat vasovagal syncope, functional AV block or functional sinus node dysfunction 15–23 …”
mentioning
confidence: 99%